AppSheet based Administration System as a Learning Simulation Media for Office Management Students - Basuki, Andi; Churiyah, Madziatul; Arief, Mohammad; Nurfaizana, Della Rulita (Journal of Applied Business, Taxation and Economics Research, 2025)
This study aims to develop and evaluate an AppSheet-based administration system, known as SIARTA, as a learning simulation media for office management students. This system is designed to provide practical experience in office administration without requiring advanced programming skills. The research process involved prototyping, conducting system trials with students, and evaluating the effectiveness and ease of use of the application. The results of the study indicate that SIARTA can improve students’ understanding of office administration in an interactive and practical way. This system has also been shown to accelerate the learning process and make it easier for students to apply administrative concepts in real life. This study shows the potential of technology in improving the quality of education and providing innovative alternatives in teaching office management. It is hoped that the results of this study can be a model for other educational institutions and contribute to the development of a more effective technology-based curriculum.